2022
DOI: 10.1021/acsomega.2c01365
|View full text |Cite
|
Sign up to set email alerts
|

Reannotation of Fly Amanita l-DOPA Dioxygenase Gene Enables Its Cloning and Heterologous Expression

Abstract: The l -DOPA dioxygenase of Amanita muscaria (AmDODA) participates in the biosynthesis of betalain- and hygroaurin-type natural pigments. AmDODA is encoded by the dodA gene, whose DNA sequence was inferred from cDNA and gDNA libraries almost 30 years ago. However, reports on its heterologous expression rely on either the original 5′-truncated cDNA plasmid or artificial gene synthesis. We provide unequivocal evidence that the heterologous expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(138 reference statements)
0
1
0
3
Order By: Relevance
“…DOPA dioxygenases (DODA) can be used to produce betalamic acid from the oxidation of l -DOPA by molecular oxygen [ 29 , 30 , 31 ]. Sekiguchi et al used the recombinant DODA of Mirabilis jalapa (L.) to synthesize amino acid betaxanthins and found that indicaxanthin (Pro-Bx) and miraxanthin V (dopamine-Bx) are less capable of reducing 1,1-diphenyl-2-picrylhydrazyl radicals (DPPH) than ascorbic acid [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…DOPA dioxygenases (DODA) can be used to produce betalamic acid from the oxidation of l -DOPA by molecular oxygen [ 29 , 30 , 31 ]. Sekiguchi et al used the recombinant DODA of Mirabilis jalapa (L.) to synthesize amino acid betaxanthins and found that indicaxanthin (Pro-Bx) and miraxanthin V (dopamine-Bx) are less capable of reducing 1,1-diphenyl-2-picrylhydrazyl radicals (DPPH) than ascorbic acid [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…[16] Betalaínas e antocianinas são pigmentos mutuamente exclusivos na natureza, ou seja, nunca foram encontradas no mesmo ser vivo e algumas espécies de fungos basidiomicetos, como o agário das moscas (Amanita muscaria), produzem betalaínas por possuírem uma DOPA extradiol dioxigenase que, embora seja estruturalmente diferente da enzima encontrada em plantas, cumpre a mesma função. [17] Betalaínas são caracterizadas pelo sistema 1,7-diazaheptametínio, um cromóforo que se origina da condensação entre o grupo aldeído do ácido betalâmico e nucleófilos de nitrogênio. [18] Esse sistema conjugado associa uma imina e uma enamina e é responsável pela cor, emissão de fluorescência, [13] propriedades redox e pelo potencial antioxidante [19,20] das betalaínas.…”
Section: Preâmbulounclassified
“…Os grupos amino e carboxila são apresentados nas formas não carregadas para maior clareza. Esquema adaptado de [17].…”
Section: Preâmbulounclassified
“…Embora a maioria das betaxantinas derivadas de aminoácidos proteinogênicos já tenha sido encontrada in vivo e/ou obtida por meio de semissíntese ou métodos biotecnológicos 50,118 , seus espectros de absorção são frequentemente adquiridos durante análises de HPLC/PDA sob condições cromatográficas específicas, 20,39,43,50,83,109,119 por exemplo, misturas acidificadas de água/MeCN. O coeficiente de absorção molar (ε) para a maioria das betaxantinas também é desconhecido, e para fins práticos, a média de 48000 L mol -1 cm -1 em 480 nm é utilizada.…”
Section: Propriedades De Absorção Uv-vis E Fluorescênciaunclassified